Non-GAAP EPS Denominator Choices - Gee, Kurt H.; Linsmeier, Thomas J.; Partridge, Clay (The Accounting Review, 2024)
ABSTRACT We provide the first evidence after Regulation G on firms’ non-GAAP EPS denominator choices and whether they are informative or opportunistic. From 2013 to 2019, 17 percent of annual non-GAAP EPS numbers use denominators different from that of GAAP diluted EPS, which makes denominator adjustments among the most prevalent individual types of non-GAAP adjustments. For firms reporting GAAP and non-GAAP profits or GAAP losses and non-GAAP profits, we provide evidence consistent with denominator adjustments increasing non-GAAP EPS informativeness. Our evidence also suggests that opportunism in denominator choices is concentrated in firms reporting GAAP losses and non-GAAP profits and failing to adjust the denominator. Such nonadjustment is inconsistent with SEC requirements to report non-GAAP EPS “on a diluted basis” because the EPS denominator for a GAAP loss excludes dilutive claims. Although the SEC largely overlooks such firms, they are more likely, on average, to report non-GAAP EPS that analysts consider inflated. JEL Classifications: M40; M41; M48.